Characterisation of anti-glycan monoclonal antibodies - Noble, Philip W. (2011)
The aims of this thesis are to establish the therapeutic value of two anti-glycan mAbs produced in-house, to develop an immunisation protocol with the aim of improving the immunogenicity tumour-associated glycolipids with the intention of producing therapeutically valuable mAbs and to determine the implication of a mAb with the ability to induce apoptosis in colorectal cancer.